International heritage and historic building conservation : saving the world's past - Atgen, Zeynep (New York : Routledge, 2013)
This text assesses contemporary conservation paradigms from around the world. It evaluates conservation case studies from previously excluded areas of the world to create an integrated account of historic building conservation that crosses the boundaries of language and culture and sets an example for further inclusive research.
List of figures -- Foreword -- 1. Introduction: global boundaries between preservation and conservation -- 2. Periphery, margins and self -- 3. Defence, survival or neglect : the role of politics -- 4. The non-European world and the bequest of modernity -- 5. Postmodernity elsewhere -- 6. Conservation funding in another world -- 7. Public participation -- Epilogue: saving the world's past -- Appendix -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: HISTORIC BUILDINGS -- CONSERVATION AND RESTORATION